Perancangan VFD Motor Induksi 1 Phase Untuk Pengaturan Awal Kecepatan Mobil Listrik - Leily Wustha Johar; S Umar Djufri; Hendi Matalata (Universitas Batanghari Jambi, 2021)
Variable speed drives and the importance of controlling the speed of existing motors have attracted much attention with the advent of new electrical devices and magnetic materials. This paper is a comprehensive review of the application of VFD in energy saving electric motors. The aim is to identify energy saving opportunities and apply variable speed drives to existing electric motor applications. In this paper the authors hope to provide useful information for future variable speed drive applications such as fans, pumps, coolers, ventilators and as electric car propulsion. In this study, a series of frequency changes has been tested as an induction motor speed regulation (VFD), which in the results of this frequency change research can regulate the speed of the induction motor. In this study, the frequency change is still regulated analogously by changing the resistor size on the PWM signal generator IC for the MOSFET driver. For that the next research is expected to change the frequency can be done digitally